KEDUDUKAN KEMENAKAN BATALI ADAT DALAM PEMBAGIAN HARTA PUSAKA TINGGI DARI MAMAK KE KEMENAKAN DI KENAGARIAN TABEK PANJANG KECAMATAN BASO KABUPATEN AGAM PROVINSI SUMATERA BARAT - Mashut Mashut; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Pusako or the property of Pusako is all tangible wealth (materil), which is inherited to the sons of niece in Minangkabau. The distribution of high estate must conform to the lineage of family ancestry (Ranji). However, the fact that occurs in the division of high heirlooms there is a conflict where one of the parties who receive a high heirloom is not suitable based on the goods. The purpose of this research is to know the position of traditional Batali's incense in the division of the high estate of Mamak to frankness in Kenagarian Tabek Panjang Sub-district of Agam Regency West Sumatera Province and to know the completion of Dispute in the division of the high estate of the Mamak to the frankness of custom Batali in Kenagarian Tabek Panjang Kecamatan Baso Regency of West Sumatera province.This type of research can be classified sociological, because in this research the author directly conducts research on the location or place studied to provide a complete and clear picture of the problem studied. This research was conducted Agarian long Tabek subdistrict Baso regency of West Sumatera Province, while the population and samples are the whole party related to the problems studied in this research, data sources Used primary data, data skunders, and tertier data, data collection techniques in this study with interviews and literature studies.The results of the study can be concluded two things. First, in the Kenagarian Tabek Panjang Kecamatan Baso Regency of West Sumatera Province, the position of indigenous Batali in the division of the high estate has less attention from the Ninik Mamak to fight for its rights. Secondly, the settlement of disputes in the division of the high estate of the Mamak to the frankness in Kenagarian Tabek Panjang District of Baso Agam Province of Sumatra is done by the procedure, namely: in a virtuous way, batanggo down, starting from Inter Ninik Mamak tribe, but if not find the bright point of the problem, then the plaintiff to appeal the level of KAN, plaintiff and defendant will present a witness. A person/tribe is forbidden to litigate the Sako and Pusako Langsungke the court without going through the procedures prescribed by ADAT.Keyword:high-heritagetreasures-Mamak